2012
DOI: 10.4049/jimmunol.1103466
|View full text |Cite
|
Sign up to set email alerts
|

Activated T Cell Exosomes Promote Tumor Invasion via Fas Signaling Pathway

Abstract: Activated T cells release bioactive Fas ligand (FasL) in exosomes, which subsequently induce self-apoptosis of T cells. However, their potential effects on cell apoptosis in tumors are still unknown. In this study, we purified exosomes expressing FasL from activated CD8+ T cell from OT-I mice and found that activated T cell exosomes had little effect on apoptosis and proliferation of tumor cells but promoted the invasion of B16 and 3LL cancer cells in vitro via the Fas/FasL pathway. Activated T cell exosomes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
177
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 234 publications
(183 citation statements)
references
References 44 publications
3
177
0
3
Order By: Relevance
“…For example, EVs from activated CD8+ T-cells can increase tumor immunogenicity by activating ERK and NFκB signaling through TNF-related signaling leading ultimately to the upregulation of MMP-9. This chain of events increases the metastatic potential in melanoma and lung cancer 11 . In another chain of events pancreatic ductal adenocarcinomas cell-derived EVs can lead to pre-metastatic niche formation in sequential steps of induction of TGFβ signaling in Kupffer cells leading to extracellular matrix modification and subsequently an influx of bone marrow-derived macrophages to the liver, providing a favorable niche for liver metastasis 19 .…”
Section: Evs Set the Place And Time For Neo-angiogenesismentioning
confidence: 99%
“…For example, EVs from activated CD8+ T-cells can increase tumor immunogenicity by activating ERK and NFκB signaling through TNF-related signaling leading ultimately to the upregulation of MMP-9. This chain of events increases the metastatic potential in melanoma and lung cancer 11 . In another chain of events pancreatic ductal adenocarcinomas cell-derived EVs can lead to pre-metastatic niche formation in sequential steps of induction of TGFβ signaling in Kupffer cells leading to extracellular matrix modification and subsequently an influx of bone marrow-derived macrophages to the liver, providing a favorable niche for liver metastasis 19 .…”
Section: Evs Set the Place And Time For Neo-angiogenesismentioning
confidence: 99%
“…Accordingly,they become more sensitive to apoptosis when they interact with cells that express the FasL on their surface (Nagata et al, 1995;Ehrenschwender et al, 2009). Evidence for this mechanism of tumor immune privilege has been provided for several cancers (Zhou et al, 2006;Wu et al, 2010;Gomes et al, 2011;Cai et al, 2012;Tian et al, 2012;Wang et al, 2012) that have been shown to express FasL, including skin, lung, breast, and cervical cancers, gastric cancer. To date, the molecular events underlying the role of Fas/FasL in the progression to oral carcinoma are poorly understood (Chen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes derived from activated T-cells were shown to promote B16 melanoma and Lewis lung cell metastasis to the lung (86). Activation of the Fas/FasL pathway in tumor cells, increase in FLICE inhibitory proteins, activation of ERK-and NFĸB signaling and the resulting increase in MMP9 activity were shown to be responsible for promotion of metastasis (124). However, most investigations on immune-mechanisms based promotion of metastasis were performed with TC-derived exosomes.…”
Section: Metastasis Promotion By Exosomes Based On Immuno-suppressionmentioning
confidence: 99%